The controverted therapeutic efficacy of Allium sativum and Artemisia herba-alba extracts on Cryptosporidium-infected mice - Enas Said Elbahaie; Reda Lamei El Gamal; Ghada Mahmoud Fathy; Asmaa Mohammed Farouk Al-Ghandour; Nadia El-Akabawy; Basma Hosny Abd El Hameed; Samah Hassan Yahia (Journal of Infection in Developing Countries)
Introduction: Cryptosporidiosis has become an issue of great interest being life-threatening among immunocompromised hosts worldwide. This study explored the curative effect of Allium sativum (garlic) and Artemisia herba-alba ethanolic extract versus Nitazoxanide drug on both immunocompetent and immunosuppressed-Cryptosporidium experimentally-infected mice.